Model for Combating Child Criminal Offenses Thru the Development of a Legal Culture Based on Pancasila - Kartika Asmanda Putri; Endang Yuliana Susilawati; Nimas Yuski Nur Laili (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The increasing number of children facing the law in Indonesia indicates that the repressive legal approach has not been fully effective in addressing juvenile crime. Children, as subjects of law, have social and psychological characteristics that differ from adults, so law enforcement against them must consider humanitarian and educational aspects. This research aims to analyze the factors causing children to commit criminal acts and formulate a model for addressing them based on developing a legal culture rooted in Pancasila values. This research employs a normative juridical method with conceptual and legislative approaches, and analyzes data qualitatively thru literature review and positive legal norms. The research findings indicate that the causes of children committing criminal acts are multidimensional, encompassing family factors, social environment, education, economics, and psychological factors. Therefore, mitigation efforts cannot be done partially, but must be thru a preventive, educational, and restorative approach. This research offers a model for overcoming challenges thru the development of a legal culture based on five main pillars: family, education, society, the state, and the legal system. This model emphasizes the importance of synergy between law enforcement and moral development in accordance with the values of Divinity, Humanity, Unity, Deliberation, and Social Justice. Thus, the development of Pancasila legal culture is expected to realize a child criminal justice system that is humanistic, substantively just, and oriented toward social rehabilitation in accordance with the legal ideals of a Pancasila state of law.